2022
DOI: 10.1097/cm9.0000000000002339
|View full text |Cite
|
Sign up to set email alerts
|

Encyclopedia of fecal microbiota transplantation: a review of effectiveness in the treatment of 85 diseases

Abstract: Fecal microbiota transplantation (FMT) has been used as a core therapy for treating dysbiosis-related diseases by remodeling gut microbiota. The methodology and technology for improving FMT are stepping forward, mainly including washed microbiota transplantation (WMT), colonic transendoscopic enteral tubing (TET) for microbiota delivery, and purified Firmicutes spores from fecal matter. To improve the understanding of the clinical applications of FMT, we performed a systematic literature review on FMT publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 141 publications
1
27
0
Order By: Relevance
“…Until now, the only routine medical application was treatment of recurrent Clostridioides difficile infection. But also, many non-infectious diseases have been extensively studied, such as inflammatory bowel diseases, the microbiota-gut-liver axis, the microbiota-gut-brain axis, and oncologic and hematological diseases [ 11 , 12 ]. The first indication of efficacy for FMT in human metabolic diseases was published in 2012, where in a pilot study in the Netherlands, in nine male adults with metabolic syndrome who received FMT from a lean donor, insulin resistance was improved, whereas no changes were observed in nine controls who received autologous FMT [ 8 ].…”
Section: Fecal Microbiota Transplantation (Fmt) For Metabolic Syndromementioning
confidence: 99%
“…Until now, the only routine medical application was treatment of recurrent Clostridioides difficile infection. But also, many non-infectious diseases have been extensively studied, such as inflammatory bowel diseases, the microbiota-gut-liver axis, the microbiota-gut-brain axis, and oncologic and hematological diseases [ 11 , 12 ]. The first indication of efficacy for FMT in human metabolic diseases was published in 2012, where in a pilot study in the Netherlands, in nine male adults with metabolic syndrome who received FMT from a lean donor, insulin resistance was improved, whereas no changes were observed in nine controls who received autologous FMT [ 8 ].…”
Section: Fecal Microbiota Transplantation (Fmt) For Metabolic Syndromementioning
confidence: 99%
“…Over the past decade, fecal microbiota transplantation (FMT) has gained growing attention due to its efficacy in gut microflora reconstruction, especially in patients with recurrent Clostridium difficile infection (CDI) [ 237 , 238 ]. Moreover, FMT has been reported as a relatively safe, well-tolerated, and successful treatment for various disorders other than CDI, with evidence in active UC being the most compelling [ 239 ].…”
Section: Current Treatments In Pbc and Pscmentioning
confidence: 99%
“…Recently, FMT's application to liver cirrhosis has been studied in detail. A thorough investigation and meta-analysis published in the Journal of Gastroenterology and Hepatology in 2020 analyzed the results of 11 randomized controlled trials involving 515 patients with cirrhosis [17]. The analysis found that FMT significantly improved the liver function, decreased the risk of hepatic encephalopathy, and reduced the incidence of bacterial infections compared to conventional treatment.…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%